Foreign exchange : a practical guide to the FX markets - Weithers, Timothy M. (Timothy Martin), 1956- (Wiley finance series., 2006)
A straightforward, rigorous, and thorough introduction to foreign exchangeBlending theory and practice, Foreign Exchange progresses from a short history of the foreign exchange market and a description of the FX Spot Market through currency forwards and other derivatives, to FX options strategies and more exotic and complex structures-making this technical information generally accessible.